PENGARUH COST OF REM TERHADAP REAL EARNINGS MANAGEMENT DENGAN ASET DAN MARKET TO BOOK VALUE SEBAGAI VARIABEL KONTROL - Tri Yulaeli (Program Studi Akuntansi, 2018)
Abstract The purpose of this study is To know how the influence of cost of rem can influence real earnings management with control variable asset and market to book value, the study population is 147 manufactured companies registered in Bursa Efek Indonesia in 2011-2016 and the sample research into 35 companies with research methods. The type of research used is associative research that is associative technique of associative research using quantitative analysis technique (statistic). To know the amount of influence between variable of writer use data analysis with help SPSS 20. The result of research proves that there is financial distress no significant to real earnings management or hypothesis (H1) rejected, institutional ownerships no significant to real earnings management or hypothesis (H2) rejected and H3 accepted means family ownerships have a negative significant to real earnings management. . Keyword :real earnings management, financial distress, institutional ownership, family ownership